Carrier frequency synchronization technology in UFMC - Lu YANG; Ping HE; Shan WANG (Dianxin kexue)
In view of the problem that the universal filtered multi-carrier（UFMC）system is sensitive to carrier frequency offset,a frequency synchronization algorithm was proposed.For the sake of keeping good features of UFMC system and reducing the complexity of filter design,the algorithm designed a pilot sequence which sub-bands are orthogonal,and used the non-linear least square algorithm（NLS）to realize the frequency offset estimate.In order to further improve the performance of algorithm in low signal to noise power ratio（SNR）environment,the receiver could process data by constructing sequence and calculating the correlation of estimated signal.Simulation results demonstrate that the designed pilot is superior to all-one pilot in terms of both bit error rate（BER）and CFO performance over additive white Gaussian noise（AWGN）and rayleigh fading channel.And in low SNR environment,the improved algorithm has better performance than NLS algorithm under CFO.